2011
DOI: 10.1561/101.00000040
|View full text |Cite
|
Sign up to set email alerts
|

>Evaluating the Consumer Response to Fuel Economy: A Review of the Literature

Abstract: How consumers evaluate trade-offs between the cost of buying additional fuel economy and the expected fuel savings that result is an important underlying determinant of the overall cost of national fuel economy standards. Models of vehicle choice are a means to predict the change in consumers' vehicle purchase patterns, as well as the effects of these changes on compliance costs and consumer surplus. This paper surveys the literature on vehicle choice models and finds a wide range in methods and results. A lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 74 publications
(173 reference statements)
4
37
0
Order By: Relevance
“…Yet the evidence on consumer valuation of fuel economy is mixed (Greene 2010;Helfand and Wolverton 2011). One study has found that consumers are indifferent between $0.76 now and $1.00 of discounted future gasoline expenditures, suggesting mild undervaluation of fuel economy that could be due to myopia (Allcott and Wozny 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Yet the evidence on consumer valuation of fuel economy is mixed (Greene 2010;Helfand and Wolverton 2011). One study has found that consumers are indifferent between $0.76 now and $1.00 of discounted future gasoline expenditures, suggesting mild undervaluation of fuel economy that could be due to myopia (Allcott and Wozny 2014).…”
mentioning
confidence: 99%
“…If firms believe consumers are myopic and therefore undervalue energy efficiency, product offerings will not be optimal from a social perspective, even if firms hold incorrect beliefs about consumer preferences. Studies of the automotive industry posit several explanations for the apparently suboptimal level of fuel economy that manufacturers provide (Helfand and Wolverton 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, high implicit discount rates for home energy investments could also be rationalized by moral hazard: contractors may provide low quality services, and consumers may use high hurdle rates to insulate themselves from this risk (Giraudet and Houde 2014). 38 Automobile purchases provide a good setting to study these questions because such purchases are major decisions, about which consumers presumably think carefully, and because the cost of gasoline has varied substantially over time (Helfand and Wolverton 2011). One study has found that consumers are indifferent between $0.76 now and $1.00 of discounted future gasoline expenditures, suggesting the possibility of myopia or undervaluation of fuel economy (Allcott and Wozny 2014).…”
Section: Does Heuristic Decision-making And/or Bounded Rationality Inmentioning
confidence: 99%
“…Automobile purchases provide a good setting to study these questions because such purchases are major decisions, about which consumers presumably think carefully, and because the cost of gasoline has varied substantially over time (Helfand and Wolverton 2011). One study found that consumers are indifferent between $0.76 now and $1.00 of discounted future gasoline expenditures, suggesting the possibility of myopia or undervaluation of fuel economy (Allcott and Wozny 2013).…”
mentioning
confidence: 99%